Russian industry intellectualization development: Strategic approach - L. S. Zelentsova; V. F. Ukolov; A. I. Tikhonov (Управление)
The current stage of industrial production digital transformation consists in developing and integrating artificial intelligence technologies. Strategic importance of Russian industry intellectualization requires synchronous involvement of all industries in this process in order to ensure effective and proportional development of the country’s economy. In this regard, the purpose of the study is to develop proposals for coordinated and balanced strategizing in the field of intellectual development of the country’s industry. The subject of the study is the relationship of digitalization processes and the use of intelligent technologies with strategies implementation for developing all industries and the Digital Economy National Program. The hypothesis of the study is based on the problem of low efficiency of implementing existing strategies of sectoral development and production digitalization processes, the causal result of which is inconsistency and imbalance of their development in time due to the lack of common views, common standards, and common space of information and communication interaction. Research objectives are to study statistical materials and practical developments in the field of industry digitalization; to analyze the current strategies for developing industrial sectors up to 2035; to analyze the processes of industry digitalization on the basis of reports on implementing the Industry 4.0 concept, various digital platforms for production dispatching, predictive analytics, etc.; to develop the concept of intelligent industrial development and the mechanism of integrating all participants in the processes of digital transformation, including the state. The authors propose the CBS concept for the development of the strategy of industry intellectualization and the mechanism of integrating subjects of the strategic process in a single space of information and communication interaction for the purposes of systematic linkage of industry development strategies on the basis of end-to-end technologies and artificial intelligence.